Gold-catalyzed synthesis of dibenzopentalenes: evidence for gold vinylidenes - Hashmi, A. Stephen K.; Wieteck, Marcel; Braun, Ingo; Nösel, Pascal; Jongbloed, Linda; Rudolph, Matthias; Rominger, Frank (Advanced synthesis & catalysis, 2012)
A series of easily accessible arene-1,2-diynes, bearing one aryl substituent on one of the alkynyl groups, is readily converted to dibenzopentalenes in good yields by gold(I) catalysts. The participation of gold acetylides could be proven by the direct conversion to the corresponding gem-diaurated dibenzopentalenes with a gold catalyst. From an experiment with a gold acetylide complex and stoichiometric amounts of the gold “catalyst” the corresponding gem-diaurated complex of a dibenzopentalene could be obtained and characterized by X-ray crystal structure analysis. Labelling studies with deuterated alkynes show the expected deuteration of the two remaining positions of the pentalene core. All this provides evidence for a dual activation mode of the reaction and gold(I) vinylidene complexes as intermediates of the catalytic cycle.
Gesehen am 06.09.2018